Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1093/glycob/9.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Salivary mucin MG1 is comprised almost entirely of different glycosylated forms of the MUC5B gene product

Abstract: The MG1 population of mucins was isolated from human whole salivas by gel chromatography followed by isopycnic density gradient centrifugation. The reduced and alkylated MG1 mucins, separated by anion exchange chromatography, were of similar size (radius of gyration 55-64 nm) and molecular weight (2.5-2.9 x 10(6) Da). Two differently-charged populations of MG1 subunits were observed which showed different reactivity with monoclonal antibodies to glycan epitopes. Monosaccharide and amino acid compositional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 26 publications
6
118
0
2
Order By: Relevance
“…Multiangle light scattering coupled to size exclusion chromatography (SEC/MALS) measurements to determine the macromolecular integrity of purified salivary MUC5B indicated that after 60 minutes of elastase exposure, at least 80% to 90% of the mucins maintained a molecular weight of approximately 38 MDa (Figure 3B), i.e., that typical of purified MUC5B (23,24). A typical dRI trace (solid lines) and the molecular mass distribution (dotted lines) in the void (V o ) volume region are shown in Figure 3B.…”
Section: Figurementioning
confidence: 99%
“…Multiangle light scattering coupled to size exclusion chromatography (SEC/MALS) measurements to determine the macromolecular integrity of purified salivary MUC5B indicated that after 60 minutes of elastase exposure, at least 80% to 90% of the mucins maintained a molecular weight of approximately 38 MDa (Figure 3B), i.e., that typical of purified MUC5B (23,24). A typical dRI trace (solid lines) and the molecular mass distribution (dotted lines) in the void (V o ) volume region are shown in Figure 3B.…”
Section: Figurementioning
confidence: 99%
“…These different mucin glycoforms are secreted in the oral cavity by physically separated salivary glands. [29][30][31][32] The production and presence of these various glycoforms of the mucins could well play a role in the adhesion of the various oral bacteria that also show a preferred localization at the various sites in the oral cavity (see below).…”
Section: Mucinsmentioning
confidence: 99%
“…Effects on purified mucins (3,(33)(34)(35) have shown the characteristics of electrostatic interactions involving carbohydrate structures such as sialic acids (3,33,35) and have not been specific for calcium (3,31). The standard methods developed for mucin purification (5,37,38) have routinely used 6 M GdmCl as a denaturing solvent to ensure the removal of associated proteins. Present results show that such treatment destroys the calcium effects in MUC5B preparations, but as the oligosaccharides remain intact this rules out their participation in the calcium-dependent effects on saliva.…”
Section: Table III Peptides Identified By Esi-ms-ms Analysismentioning
confidence: 99%